ANALYSIS OF ATTITUDES TOWARDS THE IMAGE OF AMIR TIMUR IN MUHAMMAD ALI'S EPIC NOVEL” ULUG’ SALTANAT" (TAMADDUN NURI JURNALI, 2024)
This article deals with analyses of multifaceted character of Sohibqiron in the work of “Ulug’ Saltanat” by Muhammad Ali and there will be a thorough examination of Amir Temur’s depiction. The piece will investigate how the author represents the historical figure Amir Temur, characterized by his complexity and enigma.